Covering the staple line with a polyglycolic acid sheet after bullectomy for primary spontaneous pneumothorax prevents postoperative recurrent pneumothorax - Hirai, Kyoji (J Thorac Dis, 2015)
BACKGROUND: Postoperative recurrent pneumothorax (PORP) can arise after surgery for primary spontaneous pneumothorax (PSP) that is recurrent or involves prolonged air leakage. In this study, which included 265 patients (279 cases) with PSP who underwent surgery at our department, the percentage of patients that did not experience PORP was compared between a group that underwent bullectomy alone (group A) and a group in which the staple line and the surrounding visceral pleura were covered with a PGA sheet after bullectomy (group B) in order to study the utility of PGA sheets for preventing PORP. METHODS: Among the patients with PSP who underwent surgery, the cases of 92 patients (98 cases) from Group A and 173 patients (181 cases) from Group B were reviewed retrospectively. The incidence rates of PORP in these two groups were statistically analyzed in addition to the associations between PORP and age, gender, the affected side, height, body weight, height/weight ratio, smoking habits, or the surgical procedure. RESULTS: In total, 96.7% of the patients in group B did not suffer PORP, which was significantly higher than the equivalent figure for group A (83.7%, log-rank test: P=0.0003). Moreover, among the examined parameters, only covering the staple line with a PGA sheet was found to be an independent prognostic factor (Cox regression: P=0.0003; HR =0.212; 95% CI, 0.082-0.547). CONCLUSIONS: It was revealed that when bullectomy is performed in patients with PSP, wide coverage of the staple line and the surrounding visceral pleura with a PGA sheet significantly reduces the risk of PORP.